Socio-cultural determinants of female students’ participation in school sports in Kogi State, Nigeria - Memunat Tunrayo Ajadi; Falaye Elijah Kayode (Intelektual Pustaka Media Utama, 2021)
The decline in female participation in school sports is undesirable because of the fact that it is considered to be for boys only. It is in light of this, the study was carried out to examine socio-cultural determinants of female students’ participation in school sports in Kogi State, Nigeria. The population was 3,290 female students while 310 respondents were sampled for this study. Three hypotheses were postulated and tested using inferential statistics of Chi-square to analyze the data. Questionnaire was used to collect data from the respondents. The findings show that gender, cultural and religious belief served as a significant determinant of female participation in sports. Based on the finding, it was concluded that both male and female students should be encouraged to develop right attitude towards sports participation in schools so as to enhance gender equality in sports. There is need to sensitize the general public through various agents of socialization on how to change the negative cultural belief of people towards female participation in sports.